Identification of three novel QTL for resistance to highly aggressive Canadian strains of Plasmodiophora brassicae in rutabaga cultivar ECD10 - Karim, Md. Masud; Yu, Fengqun (Frontiers in Plant Science, 2025)
Plasmodiophora brassicae, the causal pathogen of clubroot, has emerged as a significant threat to the production of Canada’s most important oilseed crop canola. The B. napus rutabaga cultivar ‘Wilhelmsburger’ (ECD10) has shown a high resistance level to Canadian P. brassicae strains. This study utilized genotyping-by-sequencing (GBS) to identify single-nucleotide polymorphism (SNP) markers for mapping QTL related to resistance to 11 P. brassicae strains in a BC1/BC1S1 population. The short reads from the GBS were assembled to the Chinese canola cultivar ‘ZS11’ reference genome. A genetic map spanning 1,812.6 cM was developed using 1,049 non-redundant SNPs identified from 92 BC1 plants. Three quantitative trait loci (QTL) were identified: Rcr13 on chromosome A02, Rcr11 on A08, and Rcr_C03-4ECD10 on C03. Rcr13 was related to resistance to four strains (2B, 8J, 5L, and 5X), explaining 14.2% to 81.7% of the phenotypic variation explained (PVE). Rcr11 was associated with resistance to eight strains (3A, 2B, 5C, 3D, 8E, 5G, 3O, and 8P), explaining 20.2% to 83.2% of the PVE. Rcr_C03-4ECD10 was linked to resistance against strain 5C, explaining 21.5% of the PVE. Thirteen genes that encode proteins related to disease resistance were found as candidate genes for three QTL. The syntenic regions of the QTL were also examined with the reference genomes of the B. rapa `Chiifu', B. oleracea `D134' and eight different Brassica napus 'Darmor', `Gangan', `No2127', `Quinta', `Shengli', `Tapidor', `Westar', and `Zheyou7'. Differential reactions of the B. napus line carrying Rcr11 or Rcr13 with those carrying the previously identified CR genes Rcr3 and Rcr9 or Rcr8 were found with the purified P. brassicae isolates. This is the first report of rutabaga-derived QTL effective against Canadian pathotypes that overcome ‘Mendel’ resistance.